2018
DOI: 10.1007/978-3-319-98788-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and Transsulfuration in Alcohol-Associated Tissue Injury and Carcinogenesis

Abstract: Glutathione (GSH) is the most abundant non-protein thiol, attaining cellular concentrations in the millimolar range. GSH functions to protect cells against endogenous and exogenous electrophiles. In addition, GSH serves as a cofactor for the GSH peroxidase family of enzymes which metabolize H2O2 as well as lipid peroxides. Through the action of glutathione S-transferase family of enzymes, GSH is conjugated to a variety of electrophilic endogenous compounds and exogenous chemicals, and thereby facilitates their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…CYP2E1, in particular, is implicated in the pathogenesis of both NAFLD and ALD in humans[ 5 , 27 ]. CYP2E1 metabolizes EtOH and other xenobiotics in a nicotinamide adenine dinucleotide phosphate (NADP + /NADPH)-mediated process and produces H 2 O 2 and O 2 – [ 28 ]. Mouse models also indicate that CYP2E1 plays a role in lipid dysregulation[ 29 ] and diabetes[ 30 ].…”
Section: Pathological Overlap Between Nafld and Aldmentioning
confidence: 99%
“…CYP2E1, in particular, is implicated in the pathogenesis of both NAFLD and ALD in humans[ 5 , 27 ]. CYP2E1 metabolizes EtOH and other xenobiotics in a nicotinamide adenine dinucleotide phosphate (NADP + /NADPH)-mediated process and produces H 2 O 2 and O 2 – [ 28 ]. Mouse models also indicate that CYP2E1 plays a role in lipid dysregulation[ 29 ] and diabetes[ 30 ].…”
Section: Pathological Overlap Between Nafld and Aldmentioning
confidence: 99%
“… 74 Ethanol tampers with the function of multiple enzymes, including MAT, BHMT, and various MTs. 76 , 77 Decreased MAT activity is attributable to alcohol-induced oxidative stress and reactive aldehydes, which can inactivate the liver-specific MAT. The lack of metabolic products due to impaired methionine metabolism inhibits remethylation of Hcy, the form of GSH, thus weakening defenses against oxidative stress.…”
Section: Methionine Metabolism and Cldsmentioning
confidence: 99%
“…The lack of PRMT causes lower PE methylation, which leads to SAM accumulation and sensitivity to oxidative stress. 73 , 74 , 76 78 , 81 83 Nonalcoholic fatty liver disease Hepatic Fgf21 mRNA was increased, which is a modulator of energy homeostasis. FFA accumulates and can cause lipotoxicity through JNK1 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde depletes GSH (glutathione) and hence intracellular redox eucrasia. Different mechanisms may participate: sequestering of GSH pools by non-enzymatic binding [72], reduction of GSH peroxidase (EC 1.11.1.9) activity [73], conjugation with GSH metabolites such as cysteinyl glycine [74,75], or disruption of the transsulfuration pathway [76]. However, in a murine experimental model of forced GSH depletion obtained by disrupting a glutamate-cysteine ligase modifier (GCLM) gene, Chen et al [77] showed that low levels of GSH protected liver tissue against the insult of ethanol by adapting the metabolic flux of several compounds to resist alcohol insult.…”
Section: Oxidative and Nonoxidative Metabolism Of Ethanolmentioning
confidence: 99%
“…The term C1 metabolism refers to the circuitry of metabolic pathways (Figure 4) essential for cell proliferation and endurance (nucleotide synthesis, Ser Gly and Met metabolism, methylation reactions, synthesis of polyamines, redox reactions, and transsulfuration pathway) that manage the provision of one-carbon modules (methyl groups) and connects with the control of the cellular redox state [76,[112][113][114][115][116]. Folate (pteroil-L-glutamate) metabolism distributes one-carbon components through redox reactions.…”
Section: Ethanol and Metabolism Of C1-unitsmentioning
confidence: 99%